500 najlepszych polskich dowcipow. - Mleczko, Andrzej; Sawka, Henryk (Koszalin : Oficyna TREND, 1991)
A collection of the best Polish jokes and one-liners, trating all sorts of subjects.
[cz. 1.] Wybor ilustracji autorstwa Andrzeja Mleczki; cz. 2. Wybor ilustracji autorstwa Henryka Sawki.
Keywords: Polish wit and humor; Polish wit and humor, Pictorial